Effects of Slash-burning on Soil Properties, Weed Growth, Taungya Yield and Growth of Teak - Chacko, K. C.; Sankar, S.; Pandalai, R. C.; Nandakumar, U. N. (Indian Forester, 1991)
A field trial was conducted at Mundakadavu of Karulai Range in Nilambur Forest Division during 1981-85 to study the effect of slasb burning on soil properties, weed growth, taungya yield and growtb of teak (Tectona grandis L.f.) in a second rotation plantatioD. Tbe study lead to tbe following conclusions. Burning caused significant enhancement of base content and change in soil reaction from acidic to alkaline. These effects were short-lived and within six months the soil had the same reaction and base content as at the start of the experiment. Though burning reduced weed growth during the first three months after planting, the difference was not significant subsequently. The yield of paddy (Oryza sativa L.), the first taungya crop, was not intlueuced by the treatments. None of the treatments had significant influence on survival of teak. The treatments effect on height of teak, noticed during the first three years, was not significant afterwards. Salvaging firewood between 10-30 em girth over bark (which would have otherwise been burned) yielded a net revenue of Rs. 756 per ha in 1982 after meeting the labour charges of Rs. 1244. As slash burning did not have lasting influence either on the growth of teak or on soil properties, a modification in the current practice is suggested. All wood down to 10 em girth over bark (the lower limit up to wbicb firewood collection may be feasible) could be salvaged and marketed and the rest either burned (resulting in a light slasb burning) or left at site to deteriorate over time.